The Performance of Anoxic Nitrification-Denitrification Process Based on Biogenic Manganese Oxide and Immobilized Biogenic Manganese Oxide Beads - Demir, Hatice; Tekay, Kubra; Tepe, Ozlem; Aksoy, Hande; Hanay, Ozge; Yildiz Sevgili, Burcin (Springer Int Publ Ag, 2026)
Ammonium is a pollutant frequently found in water bodies and has toxic effects on living things, making it necessary to eliminate ammonium from water before discharging it into surface water bodies. This study examines the ammonium nitrogen removal performance of an anoxic nitrification-denitrification process based on biogenic manganese oxide (BMO) and immobilized biogenic manganese oxide (IBMO) beads. Biogenic manganese oxide was produced using Pseudomonas putida, and alginate was used to prepare immobilized biogenic manganese oxide beads. Various analyses were conducted to characterize BMO and IBMO, and revealing that biogenic manganese oxide has an amorphous structure and exhibits dense mineral precipitation around bacterial cells, as well as particles with irregular geometric shapes. The effects of C/NH4+-N ratio, initial pH, temperature, and stirring rate on anoxic nitrification-denitrification process were investigated, and ammonium nitrogen removal efficiencies of 92% and 89% were achieved for BMO and IBMO, respectively, at C/NH4+-N ratio of 5, an initial pH of 7, a temperature of 20 degrees C, and a stirring rate of 150 rpm. Although both BMO and IBMO effectively removed ammonium nitrogen under anoxic conditions, the immobilization method allows process to operate under less sensitive environmental conditions, thereby providing higher removal efficiency.
Keywords: Ammonium nitrogen removal; Anoxic nitrification-denitrification; Biogenic manganese oxide (BMO); Immobilization